Web Developer Implementation Design Using Prototyping Method at PT. Freeport Indonesia - IACB Special Community Affairs Division (Institutional Agreements & Capacity Building) - Nelson Magal (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2026)
The advancement of information technology has encouraged PT Freeport Indonesia, particularly the Institutional Agreement & Capacity Building (IACB) sub-division, to adopt a more efficient and transparent digital system. Previously, data and reporting processes were managed manually, causing inefficiencies in coordination and documentation. This study aims to design and implement a web-based information system to optimize data, document, and communication management using the Prototyping method. The system was developed iteratively through requirement analysis, design, prototype development, and user evaluation. The results show that the system improves reporting efficiency by 65% and reduces data errors by 80%. It also provides an internal communication forum, real-time dashboard, and e-learning module to support collaboration and community capacity building. The implementation of web development technology enhances the effectiveness, transparency, and accountability of institutional activities within IACB.